Dicotomías narrativas en "El árbol" de María Luisa Bombal - BIANCO,PAOLA (Universidad de Concepción. Facultad de Humanidades y Arte. Departamento de Español, 2002)
In this article I analyze how María Luisa Bombal reflects the condition of the Hispanic woman through her social and historical textualization. In all of her literary work, there exists a constant presence of nature that comes to symbolize her feminine character intimacy and their marginal situation. In "The Tree", the author presents a dichotomic structure that polarizes the narrative into two antagonistic, hierarchic, and different forces. And, the barrier that delimits them constitutes a border that separates these two irreconcilable worlds. María Luisa Bombal reveals in this short story how the patriarchal system ignores the feminine subjectivity, and how this one achieves expression in the alienated withdrawal of nature